21. EVALUATION OF ANTITUSSIVE AND EXPECTORANT EFFECTS OF BAO PHE LINH LIQUID EXTRACT ON SWISS ALBINO MICE (Vietnam Journal of Community Medicine, 2025)
Aims: The study aims to evaluate the antitussive and expectorant effects of Bao Phe Linh liquid extract in Swiss albino mice.Subjects and methods: An experimental study was conducted on 80 Swiss albino mice, divided into four groups (control, reference, and two doses of Bao phe linh). Antitussive effects were assessed using an ammonia-induced cough model, while expectorant effects were evaluated by quantifying phenol red secretion from the trachea. Data were statistically analyzed using the t-test and presented as  ± SD with a significance level of p < 0.05.Results: Bao phe linh significantly prolonged the latency to the first cough and reduced the number of coughs in 5 minutes, with inhibition rates of 24.37% and 30.82% for the low and high doses, respectively. The phenol red secretion increased to 0.353 µg/ml (low dose) and 0.382 µg/ml (high dose) compared to 0.260 µg/ml in the control group (p < 0.01), showing comparable efficacy to N-acetylcysteine (0.404 µg/ml).Conclusions: Bao phe linh liquid extract exhibits significant antitussive and expectorant effects. Further studies are needed to evaluate its efficacy and safety in clinical settings.
Keywords: Bao phe linh; antitussive; expectorant; upper respiratory tract infections; animal experiment